2005
DOI: 10.1088/0266-5611/21/5/009
|View full text |Cite
|
Sign up to set email alerts
|

A note on the CQ algorithm for the split feasibility problem

Abstract: Let C and Q be nonempty closed convex sets in N and M , respectively, and A an M × N real matrix. The split feasibility problem (SFP) is to find x ∈ C with Ax ∈ Q, if such x exist. Byrne (2002 Inverse Problems 18 441-53) proposed a CQ algorithm with the following iterative scheme:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
121
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(123 citation statements)
references
References 15 publications
0
121
0
2
Order By: Relevance
“…As we know, the SFP has received so much attention due to its applications in intensity-modulated radiation therapy, signal processing, and image reconstruction, see Byrne [1,2], Censor [4][5][6], Ceng [3], Fan et al [7], Xu [20,21], Kraikaew and Saejung [9], Moudafi [10], Qu et al [12][13][14], Qin and Yao [11], Yang et al [16,22,27,28], Yao et al [23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, the SFP has received so much attention due to its applications in intensity-modulated radiation therapy, signal processing, and image reconstruction, see Byrne [1,2], Censor [4][5][6], Ceng [3], Fan et al [7], Xu [20,21], Kraikaew and Saejung [9], Moudafi [10], Qu et al [12][13][14], Qin and Yao [11], Yang et al [16,22,27,28], Yao et al [23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Yang [22] constructed a relaxed CQ algorithm for solving a special case of the SFP, in which he replaced them by projections onto halfspaces C k and Q k . In 2005, Qu and Xiu [13] modified Yang's relaxed CQ algorithm and the CQ algorithm by adopting the Armijo-like searches to get the stepsize.…”
Section: Introductionmentioning
confidence: 99%
“…In [7,9,10], it has been shown that the SPF (1.1) can also be used to model the intensity-modulated radiation therapy. Various iterative algorithms have been studied to solve the SFP (1.1), see, e.g., [8,14,16,18,22,25,27,[30][31][32] and the references therein. In particular, Jung [16] introduced iterative algorithms based on the Yamada's hybrid steepest descent method [28] for solving SFP (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of scholars have done a lot of meaningful research on the split feasibility problem (SFP), because the problem in signal processing and linear constrained optimization problems such as the feasible solution plays an important role (Censor, Y., et al, 2006;Byrne, C., 2002;Byrne, C., 2004.;Yang, Q., 2004.;Qu, B. & Xiu, N., 2005.;Xu, H. K., 2006.;Xu, H. K., 2010).…”
Section: Introductionmentioning
confidence: 99%